A Novel Variant of ATP5MC3 Associated with Both Dystonia and Spastic Paraplegia. Issue 2 (11th October 2021) - Neilson, Derek E.; Zech, Michael; Hufnagel, Robert B.; Slone, Jesse; Wang, Xinjian; Homan, Shelli; Gutzwiller, Lisa M.; Leslie, Elizabeth J.; Leslie, Nancy D.; Xiao, Jianfeng; Hedera, Peter; LeDoux, Mark S.; et al.
Abstract: Background: In a large pedigree with an unusual phenotype of spastic paraplegia or dystonia and autosomal dominant inheritance, linkage analysis previously mapped the disease to chromosome 2q24‐2q31. Objective: The aim of this study is to identify the genetic cause and molecular basis of an unusual autosomal dominant spastic paraplegia and dystonia. Methods: Whole exome sequencing following linkage analysis was used to identify the genetic cause in a large family. Cosegregation analysis was also performed. An additional 384 individuals with spastic paraplegia or dystonia were screened for pathogenic sequence variants in the adenosine triphosphate (ATP) synthase membrane subunit C locus 3 gene ( ATP5MC3) . The identified variant was submitted to the "GeneMatcher" program for recruitment of additional subjects. Mitochondrial functions were analyzed in patient‐derived fibroblast cell lines. Transgenic Drosophila carrying mutants were studied for movement behavior and mitochondrial function. Results: Exome analysis revealed a variant (c.318C > G; p.Asn106Lys) (NM_001689.4) in ATP5MC3 in a large family with autosomal dominant spastic paraplegia and dystonia that cosegregated with affected individuals. No variants were identified in an additional 384 individuals with spastic paraplegia or dystonia. GeneMatcher identified an individual with the same genetic change, acquired de novo, who manifested upper‐limb dystonia. Patient fibroblast studies showed impaired complex V activity, ATP generation, and oxygen consumption. Drosophila carrying orthologous mutations also exhibited impaired mitochondrial function and displayed reduced mobility. Conclusion: A unique form of familial spastic paraplegia and dystonia is associated with a heterozygous ATP5MC3 variant that also reduces mitochondrial complex V activity. Abstract : Family‐1 (partial) pedigree: symptomatic proband, father, and grandfather presented for neurological consultation. Subsequent investigations identified, in two families, a variant in ATP5MC3, which encodes a component of complex V in the mitochondrial electron transport chain. Functional studies in patient‐derived fibroblasts and drosophila support a loss of function. © 2021 International Parkinson and Movement Disorder Society